1999
DOI: 10.1152/jn.1999.81.6.2956
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Cortical Areas Related to Pain Perception From Stimulus Identification: Temporal Analysis of fMRI Activity

Abstract: In a recent functional magnetic resonance imaging study (fMRI), we reported the cortical areas activated in a thermal painful task and compared the extent of overlap between this cortical network and those activated during a vibrotactile task and a motor task. In the present study we examine the temporal properties of the cortical activations for all three tasks and use linear systems identification techniques to functionally differentiate the cortical regions identified in the painful thermal task. Cortical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 28 publications
8
49
0
2
Order By: Relevance
“…2). Apkarian et al (48) have suggested a role for BA 7 in pain intensity perception (48). Our observation cannot be explained in terms of this account, as one of the comparisons in our conjunction analysis did not involve pain.…”
Section: Posterior Parietal Cortex (Ppcmentioning
confidence: 57%
See 1 more Smart Citation
“…2). Apkarian et al (48) have suggested a role for BA 7 in pain intensity perception (48). Our observation cannot be explained in terms of this account, as one of the comparisons in our conjunction analysis did not involve pain.…”
Section: Posterior Parietal Cortex (Ppcmentioning
confidence: 57%
“…Apkarian et al (48) showed that FMRI signal change in BA 5 and 7 in response to repeated, identical, painful stimulation correlated with mean pain intensity ratings. This observation is consistent with our hypothesis that BA 7 signals prediction error.…”
Section: Posterior Parietal Cortex (Ppcmentioning
confidence: 99%
“…A recent study demonstrated that a more posterior activity was more likely associated to the pain perception, whereas areas located more anterior reflected stimulus parameters of the thermal stimulation [37]. The posterior cingulate gyrus is suggested to be involved in visuospatial and memory functions [13].…”
Section: Discussionmentioning
confidence: 99%
“…PPC is well known as an epicenter within a neurocognitive network of spatial attention (Mesulam 1999). Previous studies in humans have demonstrated that PPC can be activated by painful stimulation (Apkarian et al 1999). However, the role of PPC in pain perception remained unclear.…”
Section: Multiple Cortical Areas Are Involved In Nociception Processingmentioning
confidence: 99%